Corneal stromal pseudohypopyon in a pseudophakic patient - Agrawal, A; Pratap, VB; Suman, S; Pal, VK (Nepalese Journal of Ophthalmology, 2012)
Background: Corneal stromal pseudohypopyon is a rare entity. Case: A 65-year-old female developed a suture abscess in her pseudophakic right eye, three years after conventional extra-capsular cataract extraction with posterior chamber intraocular lens implantation. Pus from the suture abscess tracked down the corneal stromal layers and formed a pus level leading to the appearance of a corneal intra-stromal pseudo-hypopyon. Conclusion:This case is unique due to its unusual clinical presentation and highlights the fact that corneal pseudohypopyon may occur without any associated anterior chamber hypopyon or Descemet’s detachment. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5871 NEPJOPH 2012; 4(1): 174-175